Pengukuran Efisiensi Panel Surya Type Polycrystalline Berbasis Teknologi Internet of Things (IoT): Pengukuran Efisiensi Panel Surya Type Polycrystalline Berbasis Teknologi Internet Of Things (IoT) - Susanta, M H; sururi; Darmawan, E (Jurnal MESIL (Mesin Elektro Sipil), 2025)
IoT technology is widely used in various sectors such as Manufacturing, Health, Security and Transportation. In this study, IoT technology is used to measure the efficiency produced by solar panels. Efficiency is a comparison of the power produced to the capacity of the solar panel. The efficiency value of solar panels is influenced by the intensity of sunlight. The greater the efficiency value, the better. Some components include the ESP 32 Microcontroller, 20WP Solar Panel, Ina 219 Sensor and 20 Watt Resistor. The Ina 219 sensor reads the power produced by the solar panel which is connected to a 20 Watt resistor. The reading results are processed by the ESP 32 microcontroller and transmitted via the internet network to be stored in the Online application. So that the power data produced is stored automatically. Data collection was carried out for 7 days from 10:00 to 15:00. Based on the measurement results, the highest power produced by the solar panel occurred at 11:00 every day. The highest efficiency value occurred on the 3rd day at 5.97%. Meanwhile, the lowest efficiency value occurred on the 5th day at 3.73%.